Interleukin 2 receptor beta chain expressed in an oligodendroglioma line binds interleukin 2 and delivers growth signal. - Okamoto, Y (1990)
Interleukin 2 (IL-2) is a potent growth factor for T lymphocytes, playing a crucial role in the immune response. In view of the considerable evidence that the immunoregulatory cytokines (or lymphokines) also play a role in the growth and differentiation of cells in the central nervous system (CNS), we examined the operation of the IL-2 system in a cell line of CNS origin by expressing a cDNA encoding the beta chain of the human IL-2 receptor (IL-2R beta, a 75-kDa protein). When the cDNA was expressed in a human oligodendroglioma cell line, ONS-21, the IL-2R beta bound IL-2 with an affinity similar to that in lymphoid cells (Kd, approximately 2 nM). Furthermore, cell proliferation ([3H]thymidine incorporation) was stimulated by IL-2. These results demonstrate that the same cytokine receptor is functional in cells of the immune system and CNS and point to a molecular mechanism that is similar for growth-signal transduction between lymphoid and neural cells but that may be different in other cells, such as fibroblasts.